Scaling Up Development Programmes - UNDP (UNDP, 2013)
Many development organizations, national and local governments and civ il society organizations are faced with the issue of scaling up develo pment interventions — the main questions raised time and again are: a) what should be scaled up, and how it can be scaled up; b) is there a strong reason for a particular initiative to be scaled up; and c) what should be the value-added of the scaling up efforts, and how can prac titioners ensure that technological and other innovations are being in tegrated for improved development effectiveness? Answers to these ques tions depend on a host of complex realities—the relative strengths and weaknesses in national and local systems, political and economic situ ations, including vulnerability of country systems to shocks, commitme nts from development partners, power dynamics between various groups a nd stakeholders in a given country, regional and global environments. For the United Nations Country Teams (UNCT) and UNDP offices, another factor to consider is how to maximize our respective comparative advan tages. This guidance note summarizes the main conceptual thinking avai lable from development institutions and academia, and presents a simpl ified conceptual framework and roadmap for scaling up processes. It al so provides UNDP programme staff and UNCTs with practical actions and checklists to consider when designing and implementing programmes that support national scaling up initiatives, and proposes actions that ca n be undertaken at the regional and global levels. Although intended f or internal audiences, the scaling up concept and recommendations can also be used by the public and private sector, civil society and socia l entrepreneurs. This note benefited from a wide consultative process held in 2011, including practical recommendations and proposals from c olleagues at country offices and regional/global centres. Their insigh ts have been instrumental in the distillation of main recommendations presented in this note, and the individuals who provided substantive c ontributions are gratefully noted in the Acknowledgements section.